Alternative metrics - Orduña-Malea, Enrique (Henry Stewart Talks, 2023)
Models of scientific communication, MESUR project, The Altmetric movement, Understanding metrics and sources, Data sources and providers, Advantages and disadvantages, Case Study: Profesional de la Información